DEIKSIS DALAM SANGKAHAT PADA MASYARAKAT DAYAK BAKATIK PALAYO DI KABUPATEN BENGKAYANG - Cornelius Johari; Deden Ramdani; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractIndonesian has the largest variety of regional languages in all villages, one of which is the Dayak language. Beginning of the Dayak language from Austronesian language which entered from the northern part of the island of Borneo then spread eastward into the interior and islands in the Pacific and New Zealand. The Palayo Bakatik Dayak language (hereinafter abbreviated BDBP) belongs to the Bidayuhik language family (Peta Wurm and Hatorri, 1983). The characteristics of the Palayo or Ba-Inyam Bakatik Dayak languages are very similar to the Rara, Kanayatn-Satongo, and other Bakatik languages, which distinguish them only in a few vocabularies and there are also sound changes in certain words. Palayo's Dayak Bakatik Dayak oral tradition is a tradition that cannot be separated from the historical development of the culture, language, and community of the Palayo Bakatik Dayak community.Keywords: Syntax, Bakatik Palayo, Sangkahat, Dexsis.